2021
DOI: 10.3389/fphar.2021.747001
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase A or B Knockdown Reduces Lactate Production and Inhibits Breast Cancer Cell Motility in vitro

Abstract: Background: Lactate dehydrogenase (LDH) plays an important role in cancer pathogenesis and enhanced expression/activity of this enzyme has been correlated with poor prognosis. In this study we determined the expression profile of LDH-A and B in normal as well as in endocrine-resistant and -responsive breast cancer cells and the effect of their knockdown on LDH activity, lactate production, proliferation and cell motility.Methods: Knockdown experiments were performed using siRNA and shRNA. The expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…Likewise, LDHB silencing can repress maxillary sinus squamous cell carcinoma cell proliferation and invasion, and thus LDHB exerts an oncogenic function in this cancer [30]. Moreover, LDHB knockdown has been revealed to markedly reduce LDH activity and lactate generation, leading to reduced motility of BC cells [31],…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, LDHB silencing can repress maxillary sinus squamous cell carcinoma cell proliferation and invasion, and thus LDHB exerts an oncogenic function in this cancer [30]. Moreover, LDHB knockdown has been revealed to markedly reduce LDH activity and lactate generation, leading to reduced motility of BC cells [31],…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, LDHB silencing can repress maxillary sinus squamous cell carcinoma cell proliferation and invasion, and thus LDHB exerts an oncogenic function in this cancer [30]. Moreover, LDHB knockdown has been revealed to markedly reduce LDH activity and lactate generation, leading to reduced motility of BC cells [31], which has also indicated the oncogenic function of LDHB in BC. These data suggested that targeting LDHB potentiated sensitivity of BC cells to PTX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LDHA in BC tissues was significantly higher than that in adjacent tissues [ 48 , 49 ], and a 10-fold lactate was generated in 4T1 murine BC cell lines [50] . However, the LDHB was specifically expressed only in normal and endocrine-resistant BC cells [51] . The high expression of LDHA and serum LDH status were closely related to brain metastasis free survival and may be a predictor for TNBC brain metastasis [49] .…”
Section: Glycolysismentioning
confidence: 98%
“…In the glucose metabolism, high glucose content induced the expression of microrchidia family CW-type zinc finger 2 (MORC2) by activating c-MYC, which subsequently promoted MORC2 to form a complex with c-MYC to increase LDHA transcription [53] , leading to the BC cell migration. Study showed that both LDHA or LDHB knockdown inhibited the cell motility in MCF7 and MDA-MB-231 BC cell lines by reducing the phosphorylation level of ERK1/2 [51] , and exogenous lactate supplementation also increased the phosphorylation level of ERK1/2, reduced E-cadherin expression [48] , and finally enhanced the cell motility. More interestingly is that stable LDHA silencing alone in human MDA-MB-231 BC cell line with high concentrations of LDHB using lentivirus V-165 cannot change the lactic acid production, glycolytic activity, and the survival [54] , indicating that multiple isoforms such as LDHA/B are likely compensatory elements to maintain the production of lactic acid through glycolysis in tumor cells.…”
Section: Glycolysismentioning
confidence: 99%
“…Specifically, pyruvate is catabolized into lactate by LDHA. LDHA is associated with cancer progression and poor prognosis, since its overexpression promotes angiogenesis and tumor dissemination [ 109 , 110 ]. In neoplastic diseases, the high activity of LDHA produces large amounts of lactate, which is secreted by cancer cells.…”
Section: Metabolic Rewiring In Tumorsmentioning
confidence: 99%